Islamic Financial Management for SME and Sharia Startup Success: A Literature Review - Rita Nengsih; Maryam; Mahdi; Ferdi Nazirun Sijabat; Ayu Rahmi; Nur Ramisah (Fakultas Ekonomi dan Bisnis Islam, 2026)
Islamic financial management plays a central role in supporting the success and sustainability of MSMEs and sharia-based startups. This article aims to systematically review the literature on the application of sharia financial principles, such as sharia financial literacy, sharia compliance behaviour, financial innovation, and sharia financial inclusion, in improving the performance and competitiveness of MSMEs and sharia-based startups. The results of the study show that good Islamic financial literacy and behaviour, supported by access to Islamic financing and the use of Islamic fintech, contribute significantly to business growth, efficiency, and sustainability. In addition, factors such as Islamic entrepreneurial orientation, product and process innovation, and support from Islamic financial institutions reinforce the positive impact of Islamic financial management on business performance. However, challenges such as low Islamic financial literacy and limited access to financing remain major obstacles. This study recommends strengthening education, innovation, and cross-sector collaboration to optimise the role of Islamic financial management as a pillar of success for SMEs and Islamic startups in the digital economy era.